Synthesis of novel sulphonamide derivatives from tunable quinolines with computational studies - Nagesh Dhanaji Chavan; S. Sarveswari; V. Vijayakumar (Scientific Reports)
Abstract The synthesis of new quinoline-sulphonamide derivatives was accomplished through a meticulous five-step molecular assembly utilizing Suzuki, acid–amine cross-coupling reactions and N-alkylation. The integrity of each derivative was thoroughly confirmed via comprehensive spectroscopic analyses, including 1H and 13C NMR, DEPT-135, 1H-1H COSY, HSQC NMR and HRMS techniques. Subsequently, the absorbance and emission spectra of the newly synthesized derivatives were thoroughly investigated. Absorbance spectra were determined to be restricted within the range of 337 nm to 341.73 nm, with compound 10j exhibiting the maximum wavelength of 341.73 nm; conversely, emission spectra were uniformly detected within the range of 411.70 nm to 429.90 nm upon excitation at 340 nm, with compound 10f demonstrating the highest wavelength of 429.90 nm. Notably, these fluorophores displayed impressive characteristics, with high intensity and significant molar extinction coefficients; quantum yield ranging from 0.015 to 0.558 along with the highest stokes shifts in 10h compound (0.6237 × 10–4) in acetonitrile solvent. Additionally, compound 10p showed strong binding affinity and favorable pharmacokinetic properties through molecular docking studies and ADMET calculations. The electronic structure of the molecules was elucidated using techniques such as density functional theory (DFT) and molecular electrostatic potential (MEP) mapping. Additionally, the calculated global reactivity parameters provided valuable insights. Compound 10p exhibited a distinctly low energy gap compared to other compounds, demonstrating its exceptional properties. The comparison between experimental and theoretical UV–vis spectra with major contribution transition in percentage also showcased the remarkable consistency and quality of the synthesized derivatives, highlighting the significant potential of this work in the field of fluorophore and biological application.